Legal Protection For Customer Data Security In Internet Banking Systems: Evaluating Legal Frameworks for Customer Data Protection - Ayu Margareth R. Sitinjak; Martono Anggusti; Roida Nababan (International Journal of Law, Crime and Justice, 2025)
This study discusses legal protection for customer data security in internet banking systems in Indonesia, especially after the enactment of various related laws and regulations. The purpose of this study is to analyze how legal protection is applied and the legal measures that can be taken by customers if their data is not protected. The research method used is normative legal research with a qualitative approach, through data collection from secondary sources such as laws, legal literature, and official documents. The final findings show that although legal protection has improved with the existence of relevant laws, there are still challenges in its implementation. Customers have the right to file complaints and legal claims in the event of a data breach, which includes complaint procedures with banks and the Financial Services Authority. Compliance with regulations and the principles of legal justice are essential to maintaining public trust in the banking sector.